Menjelajahi Model Manajemen Mutu dalam Pendidikan: Tinjauan Literatur Komparatif dari Berbagai Konteks - Muhammad Aufa Ihsan; Xu Jia (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2026)
This study examines and compares major quality management models applied in education across diverse institutional and national contexts. While existing studies often analyze these models in isolation, limited attention has been given to their comparative functioning and contextual applicability within a unified analytical framework. Addressing this gap, the study adopts a structured narrative literature review with an interpretive and analytical approach to generate deeper conceptual insights into how different models operate. The analysis covers key frameworks, including Total Quality Management (TQM), ISO 9001:2015, the Malcolm Baldrige Criteria for Education, international Quality Assurance (QA) systems, as well as context-specific approaches such as School-Based Management (SBM) and External Quality Assurance Systems (SPME) in Indonesia. Drawing on 59 selected sources, the study employs thematic synthesis and cross-model comparison to identify patterns in governance orientation, implementation mechanisms, strengths, limitations, and contextual relevance. The findings indicate that no single model is universally effective; rather, their effectiveness depends on governance logic, institutional capacity, and contextual conditions. Models emphasizing external control and standardization tend to ensure accountability but risk compliance-driven practices, whereas internally driven and trust-based models promote continuous improvement but require strong organizational capacity. Based on these insights, the study proposes an integrative conceptual framework that positions quality management models along governance orientation and implementation drivers. The study contributes theoretically by offering a comparative and integrative perspective on educational quality management, and practically by providing strategic implications for policymakers and educational institutions in designing adaptive, context-sensitive quality assurance systems